PEMBERDAYAAN MASYARAKAT MELALUI PENANAMAN CENGKIH DI NEGERI WAKASIHU, MALUKU TENGAH - Matakena, Fransina; Pariela, Tonny D.; Koritelu, Paulus; Pelupessy, Pieter J.; Titing, Bernadus; Leiwakabessy, Jefrry. E. M.; Darakay, Jurnie; Ritiauw, Benico; Watianan, Soleman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
This article discusses community empowerment programs through diversifying innovations in agricultural product management to support food security and sustainable agriculture. This program aims to improve farmers' knowledge and skills in processing agricultural products, improve farmers' economies, and create an independent and prosperous society. Community empowerment in various community activities such as cloves is oriented towards economic sustainability. This community service activity was carried out in Wakasihu Country, West Leihitu District, Central Maluku Regency. The purpose of the activity with success indicators, community knowledge about clove cultivation techniques, changes in community behavior in using existing vacant land and the number of farmers and households actively involved in planting, planting distance and maintenance as well as techniques for maintaining clove seedlings. The methods used are socialization, seedling handover, and planting assistance. The results of the activity showed the enthusiasm of the residents and the planting of 65 clove seedlings as a form of readiness in managing long-term production crops.